2014
DOI: 10.1159/000368395
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Celiac Disease Patients Who Are Lost to Follow-Up Have a Poorly Controlled Disease

Abstract: Background: Follow-up of celiac disease (CD) patients is recommended for gluten-free diet (GFD) adherence monitoring and complication detection. We recently showed that 35% of children with CD were lost to follow-up (LTFU). We aimed to characterize LTFU population, and thus identify compliance barriers to GFD and follow-up. Methods: 50 LTFU patients were investigated using a telephone questionnaire, regarding frequency of follow-up, serology testing, and adherence to GFD (using the validated Biagi score). Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 7 publications
4
37
4
Order By: Relevance
“…10 Other factors likely affecting dietary adherence could be the intensity and organization of follow-up, the possibility to meet a dietician, the presence of comorbidities, and celiac disease in other family members. 13,16,48 However, we found no association between the adherence and presence of concomitant type 1 diabetes in the child or celiac disease in the family. In any case, our results demonstrate that excellent adherence to the gluten-free diet is also attainable in screen-detected celiac disease patients diagnosed and followed in a well-organized clinical practice.…”
Section: Discussioncontrasting
confidence: 74%
“…10 Other factors likely affecting dietary adherence could be the intensity and organization of follow-up, the possibility to meet a dietician, the presence of comorbidities, and celiac disease in other family members. 13,16,48 However, we found no association between the adherence and presence of concomitant type 1 diabetes in the child or celiac disease in the family. In any case, our results demonstrate that excellent adherence to the gluten-free diet is also attainable in screen-detected celiac disease patients diagnosed and followed in a well-organized clinical practice.…”
Section: Discussioncontrasting
confidence: 74%
“…The higher prevalence of seropositivity over against self-reported adherence could be caused by unrecognized lapses or via the slow normalization of high values. (13,(29)(30)(31). Previously Bardella et al found regular follow-up to improve adherence in adults (13) and Barnea et al reported similar finding in children (29).…”
Section: Discussionmentioning
confidence: 77%
“…(13,(29)(30)(31). Previously Bardella et al found regular follow-up to improve adherence in adults (13) and Barnea et al reported similar finding in children (29). The absence of such an association in Finland could be due to the high prevalence of the disease and good availability of gluten-free products, and the widespread knowledge of coeliac disease among physicians and food industry.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, adherence might depend more on how easy the treatment is, which can be affected by a number of factors. These include the price and availability of gluten‐free products, the education and follow‐up of the affected individuals and patient‐dependent characteristics, such as their education level and age at diagnosis . Therefore, a good availability of reasonably priced gluten‐free products and supportive healthcare systems could be considered as a prerequisite for wider scale screening for coeliac disease.…”
Section: Effects and Acceptance Of A Gluten‐free Dietmentioning
confidence: 99%